Do Required Minimum Distribution 401(k) Rules Matter, and for Whom? Insights from a Lifecylce Model - Vanya Horneff; Raimond Maurer; Olivia S. Mitchell (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Tax-qualified vehicles helped U.S. private-sector workers accumulate dollar25Tr in retirement assets. An often-overlooked important institutional feature shaping decumulations from these retirement plans is the "Required Minimum Distribution" (RMD) regulation, requiring retirees to withdraw a minimum fraction from their retirement accounts or pay excise taxes on withdrawal shortfalls. Our calibrated lifecycle model measures the impact of RMD rules on financial behavior of heterogeneous households during their worklives and retirement. We show that proposed reforms to delay or eliminate the RMD rules should have little effects on consumption profiles but more impact on withdrawals and tax payments for households with bequest motives.
urn:nbn:de:hebis:30:3-616576
Keywords: D14; G11; G50; G51; H24; 330; life cycle saving; household finance; 401(k) plan; retirement; tax policy